Identification of Virulence Genes and Antibiotic Resistance in Extraintestinal Pathogenic Escherichia coli Isolated from Broiler Carcasses Using MALDI-TOF MS - Jia-Tong Han; Yu-Xuan Tang; Si-Yi Wu; Yi-Ran Chen; Zhan-Peng Zou; Hang Zeng; Zhongjia Yu (Pathogens)
Escherichia coli contamination in poultry is a significant concern due to its potential to cause foodborne illness. The presence of extraintestinal pathogenic E. coli (ExPEC) strains in chicken carcasses can lead to severe human infections. This study investigates the prevalence, virulence, and antibiotic resistance of E. coli isolates from chicken carcasses processed in both wet market and industrial environments, with a focus on the detection capabilities of MALDI-TOF MS. A total of 119 E. coli isolates were obtained. Only a small proportion (5/119) carried enteropathogenic virulence genes. In contrast, 71.42% (85/119) of the isolates harbored multiple extraintestinal virulence genes. Among these, iucC and sitA, which are associated with systemic infections, were present in 68.24% (58/85) and 43.53% (37/85) of the isolates, respectively. Furthermore, 47.06% (56/119) of the isolates carrying at least two extraintestinal virulence genes were classified as ExPEC. Additionally, 94.6% (54/56) of ExPEC isolates were multidrug resistant (MDR), showing resistance to over three antibiotic classes, raising concerns about the spread of antibiotic resistance. MALDI-TOF MS profiling revealed significant heterogeneity among the ExPEC isolates, with no distinct clustering patterns based on processing environment or sampling site. These findings underscore the public health risks posed by ExPEC in poultry and emphasize the need for improved surveillance, stringent hygiene practices, and responsible antibiotic use in poultry production.